2000
DOI: 10.1053/euhj.2000.2150
|View full text |Cite
|
Sign up to set email alerts
|

Experiences from treatment of out-of-hospital cardiac arrest during 17 years in Göteborg

Abstract: In a survey covering 17 years of resuscitation of out-of-hospital cardiac arrest patients we found that the occurrence of ventricular fibrillation as the initially recorded arrhythmia decreased. There was an increase in age, in the proportion of females and in the use of bystander cardiopulmonary resuscitation. The interval between collapse and defibrillation was shortened. Survival changed over time with an increase until 1993 but with a decrease thereafter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(86 citation statements)
references
References 17 publications
5
76
0
5
Order By: Relevance
“…An amiodarone vs. lidocaine trial reported VF prevalence among pre-hospital cardiac arrests, of only 26% (33). Similar reports were published from Goteborg, Sweden documenting a decrease in VF prevalence of 39% over 17 years despite significant improvements in response time and rates of bystander cardiopulmonary resuscitation (34). Prevalence of PEA among sudden cardiac arrest cases rose from 6% to 26% during 1980-96 (34).…”
Section: Presenting Arrhythmia In Patients Who Suffer Sudden Cardiac supporting
confidence: 57%
See 1 more Smart Citation
“…An amiodarone vs. lidocaine trial reported VF prevalence among pre-hospital cardiac arrests, of only 26% (33). Similar reports were published from Goteborg, Sweden documenting a decrease in VF prevalence of 39% over 17 years despite significant improvements in response time and rates of bystander cardiopulmonary resuscitation (34). Prevalence of PEA among sudden cardiac arrest cases rose from 6% to 26% during 1980-96 (34).…”
Section: Presenting Arrhythmia In Patients Who Suffer Sudden Cardiac supporting
confidence: 57%
“…Similar reports were published from Goteborg, Sweden documenting a decrease in VF prevalence of 39% over 17 years despite significant improvements in response time and rates of bystander cardiopulmonary resuscitation (34). Prevalence of PEA among sudden cardiac arrest cases rose from 6% to 26% during 1980-96 (34). What are the causes of this altered prevalence and why is it important?…”
Section: Presenting Arrhythmia In Patients Who Suffer Sudden Cardiac supporting
confidence: 55%
“…Even when return of spontaneous circulation (ROSC) is achieved, more than half of the survivors suffer serious neurologic dysfunction. [1][2][3] New therapeutic strategies are needed to improve patient survival and outcomes. Hydrogen sulfide (H 2 S) has been shown to have a variety of protective actions in various models of tissue and organ injury.…”
Section: Introductionmentioning
confidence: 99%
“…In a significant proportion of patients, SCD can present without warning or a recognized triggering mechanism. The mean age of those affected is in the mid 60s, and at least 40% of patients will suffer SCD before the age of 65 [14].There is also strong evidence from studies in North America and Europe that there are significantly altered trends in the presenting arrhythmia observed by first responders among SCD cases [23,24]. The prevalence of SCD cases presenting with VF is decreasing with a corresponding increase in the proportion of cases presenting with pulseless electric activity (PEA).…”
Section: Sudden Cardiac Deathmentioning
confidence: 95%